Recurrence of hepatitis C after liver transplantation is associated with increased systemic IL-10 levels - Patricia A. Sheiner; Sander S. Florman; Sukru Emre; Thomas Fishbein; Myron E. Schwartz; Charles M. Miller; Peter Boros (Hindawi Limited, 2001)
Background: Recurrence of hepatitis C after liver transplantation is an almost universal occurrence. T-cell derived cytokines have an important role in the development of liver damage associated with chronic hepatitis C, their post-transplant levels, however, have not been correlated with histologic recurrence of the disease.